Exploring and Criticizing Students’ Artwork as a Learning Media in General English Instruction - Sukarni, Sri; Siswana, Siswana; Jumadil, Jumadil (Journal of Languages and Language Teaching, 2024)
The use of students’ artwork as learning media in General English courses is becoming more widely acknowledged for its many advantages. In order to clarify the significant and the implication of students’ artwork as learning media, this research was conducted. The research questions, namely: 1) what type of students’ artwork is chosen as learning media in General English courses? 2) How is the process of teaching using student artwork as a learning media? 3) what are the advantages of using student’ artwork as a learning media? This research employed a qualitative case study approach. Data were taken from the result of interview to the five students of Fine Arts study program as the respondents then analyzed in percentage and NVivo 12 analysis. It is concluded that student’s artwork as a learning media should be chosen based on students’ preference. In relation to students’ preference, paintings and sculptures are chosen as learning media in General English courses. The choice of artwork as learning media can increase motivation which helps students learn vocabulary, grammar, writing and speaking more quickly and eventually enables them to communicate in English. Accordingly, when students used artwork as learning media for learning English, they simultaneously advance their understanding of the arts and acquire practice speaking English as a foreign language. Therefore, further investigation is recommended to provide an understanding the implication of students’ artwork as learning media. The research has limitation because it focused only on the English instruction. but did not address assessment using artwork. Therefore, further investigation is recommended to provide an understanding the implication of students’ artwork as learning media.